The Disney princess cookbook - Littlefield, Cindy A., 1956- (Disney princess (Disney Press), 2013)
Collects kid-friendly recipes inspired by the adventures of favorite Disney princesses and provides step-by-step instructions and helpful cooking tips for preparing such options as Rapunzel's frying pan eggs and Ariel's sea turtle cupcakes.